HUBUNGAN ANTARA RIWAYAT PERSALINAN PREMATUR DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH DI RUMAH SAKIT UMUM PRINGSEWU TAHUN 2014 - Rohani, Siti; Wahyuni, Rini (Bappeda Kabupaten Pringsewu, 2017)
The death of rate on baby based on WHO was 35/1000 from the birth of rate in 2012. Based on Survey Demografi dan Kesehatan Indonesia in 2012 the death of rate was 32/1000 from the birth of rate. In Lampung, birth of rate in 2012 was 30/1000 from the birth of rate. Health Department Regency Of Pringsewu, the death of rate on baby in Regency of Pringsewu 9/1000 from the birth of rate up to October 2012. The great cause was Low Birth Weight. On the baby, Low Birth Weight death before birth was 8 times larger than normal’s baby. The objective of this research was known the relationship between the history of premature childbirth with the case of Low Birth Weight in General Hospital Of Pringsewu 2014. This research use analytic method with crossectional approach. The population in this research was all the new born baby who was born in General Hospital Of Pringsewu in 2014 they were 988 respondents and to get the samples use systematic random sampling technique which the total was 285 respondents. The measuring instrument in this research use checklist and analysis technique data’s they were univariate and bivariate which use experiment statistic Chi-square with computerization. The result of this research was based in univariate analysis from 285 responden, 170 babies who was born with the Low Birth Weight and 161 mothers had the history of premature childbirth. The result of bivariate analysis with Chi-square analysis between the history of premature child birth with the case of Low Birth Weight was gotten p-value 0,00 < α 0,05 meant Ha was accepted hence there was the relationship between the history of premature child birth and the case of Low Birth Weight in General Hospital Of Pringsewu 2014, with OR 2,601 it meant the mother who has the history of premature child birth has possibility 3 times larger to get Low Birth Weight. The conclution of this research is there is relationship between the history of premature child birth and the case of Low Birth Weight. Hence for the pregnant mother gets ancheck up routinely to get early detection avoiding Low Birth Weight, and the need of nutrient for the pregnant mother to sufficient too